Manual of energy saving in existing buildings and plants - Baron, Stephen L. (New Jersey : Prentice-Hall, 1978)
The manual is based on Guidelines for saving energy in existing buildings, issued in 1975 under a grant from the office of energy conservation and environment, federal energy administration.
Chapter 1. How to use this manual -- Chapter 2. Heating -- Chapter 3. Cooling -- Chapter 4. HVAC distribution systems -- Chapter 5. Domestic hot water -- Chapter 6. Heat reclamation -- Chapter 7. Lighting -- Chapter 8. Power -- Chapter 9. Central control systems --Chapter 10. Alternative energy sources -- Chapter 11. Economic analysis.
Includes index.
Keywords: ENERGY SAVING -- MANUAL